Field notes contributed by Randall Pinkston, fall 1991 - Pinkston, Randallet al (1991)
List of birds and locations contributed by Randall Pinkston. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1991. Epson - sheet feed